Inverse neutrosophic mixed graphs - Thempaavai Jayaprakash; Antony Cripsin Sweety Charles Selvaraj (Journal of Fuzzy Extension and Applications)
This article successfully attempts to introduce the notion of Inverse Neutrosophic Mixed Graphs (INMG) together with its applications. This novel approach highlights the network modeling of real physical situations with indeterminacy. Here, INMG are developed with both directed and undirected relationships between nodes that express the circumstances where the truth membership degrees of the edges are superior or equivalent to the least of the truth membership degrees of the associated vertices and where false membership and indeterminacy values of the edges are inferior or equivalent to the maximum of false membership and indeterminacy values of the corresponding vertices. Furthermore, some fundamental functions and algebraic characteristics of INMG are examined to attain a profound insight into the properties and applications. To illustrate the application of INMG, the article provides a numerical example centered around social networks. By employing INMG in this context, the article demonstrates how the model can effectively capture and represent the complex relationships within social networks, taking into account the inherent uncertainties and indeterminacies present in such systems.